2013
DOI: 10.1093/gerona/glt139
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cumulative Depressive Symptom Burden and Risk of Cognitive Decline and Dementia Among Very Old Women

Abstract: Long-term cumulative depressive symptom burden was associated with cognitive decline and risk of dementia or MCI. Older adults with a history of depression should be closely monitored for recurrent episodes or unresolved depressive symptoms as well as any cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 36 publications
4
44
0
2
Order By: Relevance
“…Moreover, we excluded possible genetic bias that could influence the response to SSRIs treatment and we verified all possible confounders that could affect statistical analysis. However, we did not consider significant MMSE score differences at follow-up as a confounder because a long-term cumulative depressive symptom burden on cognitive decline has been already described [76]. Notwithstanding these strengths, some limitations of the present study should be acknowledged.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we excluded possible genetic bias that could influence the response to SSRIs treatment and we verified all possible confounders that could affect statistical analysis. However, we did not consider significant MMSE score differences at follow-up as a confounder because a long-term cumulative depressive symptom burden on cognitive decline has been already described [76]. Notwithstanding these strengths, some limitations of the present study should be acknowledged.…”
Section: Discussionmentioning
confidence: 89%
“…One found an association between depressive symptoms and change in MMSE scores over 13 years; however, this association lost significance when adjusted for potential confounders (13). Other studies have found associations between persistent depressive scores over time and greater risk of cognitive decline (18, 20), specifically, with declines in verbal knowledge and fluency, attention, and memory (8, 10). Unlike ours, these previous studies either dichotomized depression scores from the CES-D or the Geriatric Depression Scale (8, 10) or examined measures of global cognitive function rather than specific cognitive domains (18, 20).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have found associations between persistent depressive scores over time and greater risk of cognitive decline (18, 20), specifically, with declines in verbal knowledge and fluency, attention, and memory (8, 10). Unlike ours, these previous studies either dichotomized depression scores from the CES-D or the Geriatric Depression Scale (8, 10) or examined measures of global cognitive function rather than specific cognitive domains (18, 20). Conversely, associations have been found between baseline levels of immediate and short-term verbal memory, verbal abilities, and mental tracking with persistent depression (17).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations